Late Paleozoic and Late Triassic limestones from North Palawan Block (Philippines): Microfacies and paleogeographical implications - Kießling, Wolfgang; et al. (Facies, 2000)
Selected Late Paleozoic and Triassic limestone exposures were studied on northern Palawan Island, Philippines, with regard to microfacies, stratigraphy and facies interpretation. Although some of the outcrops were already reported in literature, we present the first detailed microfacies study. Late Paleozoic carbonates in the El Nido area are represented by widley distributed Permian and locally very restricted Carboniferous limestones. Of particular interest is the first report of Carboniferous limestones in the Philippines dated by fossils. Fusulinids indicate a 'Middle' Carboniferous (Moscovian-Kasimovian) age of the Paglugaban Formation only known from Paglugaban Island. The Permian Minilog Formation consists mostly of fusulinid wackestones and dasycladacean wacke-/packstones. Fusulinid datings (neoschwagerinids and verbeekinids) provide a Guadalupian (Wordian-Capitanian) age. The depositional setting of the Middle Permian carbonates corresponds to a distally steepened ramp with biostromes built by alatoconchid bivalves locally associated with richthofeniid brachiopods. Late Triassic limestones occur in isolated exposures on and around Busuanga Island (Calamian Islands). The age of the investigated carbonates is Rhaetian based on the occurrence of Triasina hantkeni Majzon. Microfacies data indicate the existence of reefs (Malajon Island) and carbonate platforms (Kalampisanan Islands, Busuanga Island, Coron Island). Reef boundstones are characterized by abundant solenoporacean red algae, coralline sponges and corals. Platform carbonates yield a broad spectrum of microfacies types, predominantly wacke- and packstones with abundant involutinid foraminifera and some calcareous algae. These facies types correspond to platform carbonates known from other parts of Southeast Asia (Eastern Sulawesi and Banda Basin; Malay Peninsula and Malay Basin). The Philippine platform carbonates were deposited on and around seamounts surrounded by deeper water radiolarian cherts. The new data on facies and age of the Philippine Permian and Triassic carbonates contradict a close paleogeographical connection between the North Palawan Block and South China and arise problems for the currently proposed origin of the North Palawan Block at the paleomargin of South China. We hypothesize that North Palawan was part of the Indochina Block during the Carboniferous and Permian, separated from the Indochina Block during the Middle Permian and collided with the South China Block in the Late Cretaceous.
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IGM.LP.latepa
Keywords: Carbonate ramps and platforms; Carboniferous; Late Triassic; Microfacies analysis; Middle Permian; Paleogeography; Philippines (Palawan); Reefs